Clinical and molecular characterization of a patient with interstitial 6q21q22.1 deletion - Tassano, Elisa (Mol Cytogenet, 2015)
BACKGROUND: Interstitial 6q deletions, involving the 6q15q25 chromosomal region, are rare events characterized by variable phenotypes and no clear karyotype/phenotype correlation has been determined yet. RESULTS: We present a child with a 6q21q22.1 deletion, characterized by array-CGH, associated with developmental delay, intellectual disability, microcephaly, facial dysmorphisms, skeletal, muscle, and brain anomalies. DISCUSSION: In our patient, the 6q21q22.1 deleted region contains ten genes (TRAF3IP2, FYN, WISP3, TUBE1, LAMA4, MARCKS, HDAC2, HS3ST5, FRK, COL10A1) and two desert gene regions. We discuss here if these genes had some role in determining the phenotype of our patient in order to establish a possible karyotype/phenotype correlation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13039-015-0134-7) contains supplementary material, which is available to authorized users.